miR-146a is a critical target associated with multiple biological pathways of skin aging - Stafa, Klodjan; Rella, Antonella; Eagle, Whitby; Dong, Kelly; Morris, Kelsey; Layman, Dawn; Corallo, Krystle; Trivero, Jacqueline; Maidhof, Robert; Goyarts, Earl; Pernodet, Nadine (Frontiers in Physiology, 2024)
The skin is the largest organ of the human body and fulfills protective, immune, and metabolic functions. Skin function and barrier integrity are actively regulated through circadian rhythm-associated genes and epigenetic mechanisms including DNA methylation/demethylation, histone acetylation/deacetylation, and microRNAs. MicroRNA-146a-5p (miR-146a) has been associated with immune activation and skin inflammation; however, the role of miR-146a in regulating skin aging is an open question. This study investigated the role of miR-146a in fibroblasts obtained from different donors in the context of aging, and a potential association of this miRNA with circadian rhythm.Methods: Normal human dermal fibroblasts (NHDFs) from 19y, 27y, 40y, and 62y old were used to analyze for miR-146a expression. Expression of miR-146a was down-regulated with the has-mirVana miR-146a inhibitor, and up-regulated with an extract from Adansonia digitata. Effects on markers of skin aging, including cell proliferation, production of Collagen-1 and inflammatory cytokines were assessed.We show that the expression of miR-146a decreases with age in dermal fibroblasts and inhibition of miR-146a in 19y and 62y old NHDFs induced significant changes in essential clock genes indicating an association with circadian rhythm control. Furthermore, downregulation of miR-146a results in a reduction of cellular proliferation, Collagen-1 production, as well as an increase in DNA damage and proinflammatory markers. Activation of miR-146a with the Adansonia digitata extract reduced the deleterious effects seen during miR-146a inhibition and increased miR-146a transport through exosome transfer.Conclusions: miR-146a interacts with multiple biological pathways related to skin aging, including circadian rhythm machinery, cell-to-cell communication, cell damage repair, cell proliferation, and collagen production and represents a promising target to fight skin aging. Adansonia digitata extract can promote miR-146a expression and therefore support skin cells' health.